New species and records of saxicolous lichens from the Kodar Range (Trans-Baikal Territory, Russia) - Sergey Chesnokov; Liudmila Konoreva; Alexander Paukov (Plant and Fungal Systematics, 2018)
Fifty-six species of saxicolous lichens are reported for the first time from the Kodar Range. Circinaria scyphulifera is described as new to science. Aspicilia nikrapensis and Fuscidea submollis are new for Russia; Aspicilia sublapponica , Lepra monogona and Thelignya lignyota are new for southern Siberia; and 35 species of saxicolous lichens are reported for the first time for the Stanovoye Nagor’e highlands. Fuscopannaria ahlneri alredy appears in the Red Data Book of the Trans-Baikal Territory.